An Analyses of Exchange Rate Volatility: A Case of SANE Countries - Chile, Nzeh Innocent; Jane, Akaolisa Chidiogo; Eze, Millicent Adanne; Okaf, Bartholomew O.N; Yusuf, Abubakar (The Economics and Finance Letters, 2021)
The sensitivity of exchange rate to an economy has made the study of its volatility essential and that motivated this study in SANE countries. Using GARCH models under different error distributions and monthly data spanning a period of 2016-2020, findings of our study show that exchange rate is volatile in each of the countries sampled. We also found that while some models in each country exhibit mean reversion, others show none mean reversion. The asymmetric parameters of the models show that exchange rate volatility in SANE countries exhibits both positive and negative shocks. Finally, our findings show that other error distributions perform better than the traditional Normal distribution. We therefore recommend that monetary authorities in each of the SANE countries should fine tune their policies on exchange rate to ensure stable and realistic exchange rate regimes which do not hurt the macroeconomic environment. We also suggest that in modelling exchange rate volatility, each country should explore several error distributions so as to avoid biased outcomes.